2012
DOI: 10.1080/09064702.2013.783619
|View full text |Cite
|
Sign up to set email alerts
|

Environmental life cycle assessment of cereal and bread production in Norway

Abstract: Norway 14We assessed the environmental cost of producing bread, as delivered to the consumer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
3
15
3
Order By: Relevance
“…The selection of the types of a.is showed to have significant role for varying the scores for freshwater ecotoxicity (SI, Table S3-S5). Roer et al (2012) and Korsaeth et al (2012) reported a higher equivalent ecotoxicity than this study. The main reason was the assumed system boundary that was able to cover the emissions related to applied pesticides and use of different active ingredients compared to this study.…”
Section: Other Impact Categoriescontrasting
confidence: 59%
See 1 more Smart Citation
“…The selection of the types of a.is showed to have significant role for varying the scores for freshwater ecotoxicity (SI, Table S3-S5). Roer et al (2012) and Korsaeth et al (2012) reported a higher equivalent ecotoxicity than this study. The main reason was the assumed system boundary that was able to cover the emissions related to applied pesticides and use of different active ingredients compared to this study.…”
Section: Other Impact Categoriescontrasting
confidence: 59%
“…In contrast, Mondelaers et al (2009) reported a lower carbon footprint for wheat production in Europe (approximately 293 kg CO2eq/ t DM). The impact for winter wheat were even higher up to 735-879 kg CO2eq/t DM of the grain (Korsaeth et al, 2012;Roer et al, 2012), even with the straw incorporated to field. The impact calculated for the removed straw in the same study was 270 kg CO2eq/t DM.…”
Section: Other Impact Categoriesmentioning
confidence: 96%
“…Although some studies have indicated that diesel combustion is the major source of global warming impacts on soybean production [50,51], the results of the present LCA confirmed the impacts reported by Pelletier et al [48]. The GWP intensity of agricultural machinery production, which is the primary contributor to GHG emissions in farm capital [52], accounted for 73% of the total GWP in fixed and common costs.…”
Section: Global Warming Impact In the Modeled Farmsupporting
confidence: 86%
“…Few LCA studies of bread have been carried out within the Nordic region in recent years, although there have been two. One of these, a study in Norway [13], found GHG emissions to be 0.937 kg CO 2 -eq/kg of bread from cradle to consumer. The other, a Danish study [14] of rye bread, showed a result of 0.73 kg CO 2 -eq/kg of bread from cradle to consumer.…”
Section: The Environmental Impact Of Breadmentioning
confidence: 99%